Using authentic materials to improve reading comprehension of English majored students: an experimental research project at a college in Nam Dinh = Sử dụng tài liệu nguyên bản để phát triển khả năng đọc hiểu cho sinh viên chuyên ngành Tiếng Anh: nghiên cứu thực nghiệm tại một trường cao đẳng ở Nam Định - Phạm, Thị Hồng Hiếu (2020)
Based on teaching experience at Nam Dinh College of Education (NCE), the researcher has found that English majored students in our college seem to be bored with the reading texts in the course book and unmotivated to learn, and even lack vocabulary and background knowledge of real life. Therefore, the present experimental research recruiting 30 second year English majored students at NCE was conducted to explore the effectiveness using authentic materials to improve the students’ reading comprehension. They were then assigned to be an experimental group and a control group (15 students per each). During the treatment of 8 weeks, the experimental group was exposed to authentic materials. Pretest and posttest were conducted in a pair sample T-test as means to distinguish the difference of reading comprehension between the two groups. Next, follow-up semi-structured interviews were carried out with 15 students from experimental group to investigate their satisfaction level toward the lesson as well as their difficulties in reading the authentic materials. The study results emphasized the research hypothesis that authentic materials make significant improvement students’ reading comprehension. Consequently, the findings in this study result in some pedagogical implications for teachers and students to improve students’ reading comprehension. The research might be useful for English language teachers, students as well as researchers.